Prodrugs of the Archetypal Dynamin Inhibitor Bis‐T‐22. (9th November 2022) - Odell, Luke R.; Robertson, Mark J; Young, Kelly A; McGeachie, Andrew B.; Quan, Annie; Robinson, Phillip J.; McCluskey, Adam
Abstract: The Bis‐T series of compounds comprise some of the most potent inhibitors of dynamin GTPase activity yet reported, e. g., (2 E, 2′ E )‐ N, N ′‐(propane‐1, 3‐diyl)bis(2‐cyano‐3‐(3, 4‐dihydroxyphenyl)acrylamide) (2 ), Bis‐T‐22. The catechol moieties are believed to limit cell permeability, rendering these compounds largely inactive in cells. To solve this problem, a prodrug strategy was envisaged and eight ester analogues were synthesised. The shortest and bulkiest esters (acetate and butyl/ tert ‐butyl) were found to be insoluble under physiological conditions, whilst the remaining five were soluble and stable under these conditions. These five were analysed for plasma stability and half‐lives ranged from ∼2.3 min (propionic ester 4 ), increasing with size and bulk, to greater than 24 hr (dimethyl carbamate 10 ). Similar profiles where observed with the rate of formation of Bis‐T‐22 with half‐lives ranging from ∼25 mins (propionic ester 4 ). Propionic ester 4 was chosen to undergo further testing and was found to inhibit endocytosis in a dose‐dependent manner with IC50 ∼8 μM, suggesting this compound is able to effectively cross the cell membrane where it is rapidly hydrolysed to the desired Bis‐T‐22 parent compound. Abstract : The Bis‐T series of compounds comprise some of the most potent inhibitors of dynamin GTPase activity yet reported, such as Bis‐T‐22 (2 ). The catechol moieties are believed to limit cell permeability, rendering these compounds largely inactive in cells. To solve this problem, a prodrug strategy was envisaged, and eight ester analogues were synthesised. Prodrugs, e. g., 4, of 2 effect a rapid and full block of endocytosis, whereas the parent 2 is cell impermeable.